MANAGEMENT MODEL OF SCHOOL’S DENTAL HEALTH EFFORT (UKGS) OF INFORMATION SYSTEM-BASED IN IMPROVING THE QUALITY OF DENTAL HEALTH MANAGEMENT AT ELEMENTARY SCHOOL - Supriyana, Supriyana; Rasipin, Rasipin; Suryo, Galuh Ayuning (Postgraduate Program , Poltekkes Kemenkes Semarang, 2020)
ABSTRACTBackground: Dental and oral health services for elementary school students aged 6 to 12 years that have not been optimal. This show that the implementation of UKGS has not succeeded. Monitoring and evaluation on the implementation of UKGS is difficult because the reporting system of UKGS all this time is conducted manually at the end of the year using form combined with the report of the health center. The website-based UKGS management model is an information system that can be used to report the activities of UKGS directly and to monitor as well as evaluate the activities of UKGS to fit the targets that have been set.Objective: Produce innovations of the UKGS management model with relevant / appropriate information systems to increase the effectiveness and the efficiency in the implementation of UKGS in elementary school students. Methods: Research and Development (R&D) and model trials using the method of pre-experimental. The respondents amounted to 48 populations which consist 24 dental therapist and 24 UKS teachers to assess the quality of E-UKGS management and the quality of information systems in the implementation of UKGS management. The result of design of the model were tested for validation by expert. The data were tested using paired difference test, proportion test, and linear regression test.Result: Validation by expert result the average value of 92, the category is very feasible, and with a p-value of 0,014. The quality of E-UKGS management after intervention has improved compared to before (p = 0.001). Respondent’s assessment stated that the quality of E-UKGS information system in the good category. Conclusion: The UKGS management model of elementary school based on information systems provides a significant increase in the quality of UKGS management and the quality of information systems in the good category.Key Words: Elementary school students, UKGS management model, information systemABSTRAKLatar Belakang: Pelayanan kesehatan gigi dan mulut pada anak sekolah dasar usia 6 s.d 12 tahun belum optimal. Hal tersebut menunjukkan bahwa pelaksanaan UKGS belum berhasil. Selama ini monitoring dan evaluasi pada pelaksanaan UKGS sulit dilakukan karena sistem pelaporan UKGS dilakukan secara manual pada akhir tahun menggunakan formulir yang dikombinasikan dengan laporan pusat kesehatan. Model manajemen UKGS berbasis website merupakan sistem informasi yang dapat digunakan untuk melaporkan kegiatan UKGS melakukan monitoring serta evaluasi kegiatan UKGS secara langsung agar sesuai target yang telah ditetapkan.Tujuan: Menghasilkan inovasi model manajemen UKGS dengan sistem informasi yang relevan/layak untuk meningkatkan efektivitas dan efisiensi dalam pelaksanaan UKGS pada anak sekolah dasar.Metode: Research and Development (R&D) dan uji coba model menggunakan metode pre-eksperimen design. Responden berjumlah 48 yang terdiri dari 24 perawat gigi dan 24 guru UKS untuk menilai kualitas manajemen UKGS dan kualitas sistem informasi dalam E-UKGS. Hasil rancang bangun model diuji validasi oleh para ahli. Data hasil uji model diuji menggunakan uji beda berpasangan, uji proporsi, dan uji regresi.Hasil: Uji validasi ahli terhadap model E-UKGS ini didapatkan nilai rata-rata 92, kategori sangat layak, dan dengan p-value 0,014. Kualitas manajemen E-UKGS setelah perlakuan meningkat bermakna dibandingkan sebelumnya (p=0,001). Penilaian responden sebagian besar menyatakan bahwa kualitas sistem informasi E-UKGS dalam kategori baik. Kesimpulan: Penerapan model manajemen UKGS sekolah dasar berbasis sistem informasi memberikan peningkatan yang signifikan pada kualitas manajemen UKGS dan kualitas sistem informasi dalam kategori baik dibandingkan dengan sebelumnya.Kata Kunci: Anak sekolah dasar, model manajemen UKGS, sistem informasi